Authority: Divine or Qur'anic? (American Journal of Islam and Society, 1996)
Any study of authority will need to consider the subject from a numberof different perspectives, including an analysis of concepts and howbese are formulated, and a study of the effects of these concepts at boththe practical and theoretical levels. The study that ensues does not claimto be the last word on the subject. Rather, its purpose is to open the doorto further examination and inquiry and to critically analyze the main concept,in addition to the network of concepts attached to and contingentupon it.I shall not spend a great deal of time analyzing the lexical aspects of theconcepts we are about to study, because terms and concepts are two differentthings. In a study of terminology, it might suffice to identify the lexicalroot and its particular meanings and then move on to a discussion of theusages appropriate to a particular field, subject, or science. Thereafter, onemight attempt to define the term in a way that gives a clear idea of itsintended meaning. A concept, however, may be described as a term connectedto a network of philosophical and culhual roots. Furthermore,regardless of the diversity of its roots, a concept will always correlate withthe epistemological paradigm in which it functions. Certainly this assumptionholds true in regard to Islamic concepts or those concepts that are keyto an understanding of the Islamic order.Surrounding the Islamic concept of divine authority, for example,there is an entire network of related concepts. Unless these related conceptsare understood, both on their own and within the larger context ofthe Islamic order itself, the concept of divine authority will remainunclear. This network includes, for example, the concepts of divinity, creation,worship, the world and the hereafter, the divine discourse, the lawfuland the unlawful, the classification of texts as relative or unqualified or ...